Postorgasmic Illness Syndrome (POIS) in a Chinese Man: No Proof for IgE‐Mediated Allergy to Semen. (29th January 2015) - Jiang, Nannan; Xi, Guangpeng; Li, Hongjun; Yin, Jia
Abstract Introduction Postorgasmic illness syndrome (POIS) is a rarely described syndrome characterized by transient flu‐like symptoms and cognition disorders. Recent studies suggest that immunogenic reactivity to autologous semen is the underlying mechanism in POIS. However, there are no data published on immunoglobulin E (IgE)‐mediated allergy to autologous semen in men without POIS. Aim The purpose of the current work was to characterize the first diagnosed POIS patient in China and to study the allergic response of autologous semen in the affected patient and in three healthy males. Methods Specific IgE was tested with seminal fluid and common perennial aeroallergens in vitro. Skin prick tests and intracutaneous tests with autologous diluted semen were performed in the patient and three healthy donors. The pattern of IgE reactivity to patient's semen was identified using immunoblotting and ELISA. Main Outcome Measure Clinical features of POIS, skin reactions with autologous diluted seminal fluid, and the IgE reactivity patterns of immunoblotting and ELISA in vitro. Results A patient was diagnosed with POIS. The patient complained of lifelong premature ejaculation symptoms and allergic rhinitis. Routine laboratory and hormonal assessments were generally within normal range. The patient had a positive skin test with his own semen. Three healthy donors also showed positive skin tests. No semen‐specific IgE to autologous semen was detected in the serum of the affected patient or healthy males. Conclusions This is the first report of a man with POIS in China. He had positive skin reactions after injection of autologous seminal fluid but no detectable serum concentrations of specific IgE antibodies. IgE‐mediated semen allergy in men may not be the potential mechanism of POIS. Jiang N, Xi G, Li H, and Yin J. Postorgasmic illness syndrome (POIS) in a Chinese man: No proof for IgE‐mediated allergy to semen. J Sex Med 2015;12:840–845.